The role of squamous cell carcinoma antigen as a prognostic and predictive factor in carcinoma of uterine cervix - Jeong, Bae Kwon (The Korean Society for Radiation Oncology, 2011)
PURPOSE: Although the role of squamous cell carcinoma antigen (SCC-Ag) as a predictive and prognostic factor for uterine cervical cancer has been identified in previous studies, 1) the effective patient group of screening for recurrence with SCC-Ag, 2) the relationship between SCC-Ag and recurrence site, and 3) the relationship between the change of SCC-Ag and treatment outcome or recurrence have not been described. MATERIALS AND METHODS: The study included 506 patients with histologically proven uterine cervical cancer between January 1994 and December 2010. We determining the serum SCC-Ag level before treatment and after treatment, and conducted a retrospective review of the patients' records. We evaluated the sensitivity and specificity of SCC-Ag for the detection of tumor recurrence by comparing biochemical recurrence with clinical recurrence. RESULTS: The pretreatment SCC-Ag level and the proportion of patients over 1.5 ng/mL were higher in poor prognostic patient group. In the univariate and multivariate analysis, pretreatment SCC-Ag showed a statistically significant correlation with tumor size, International Federation of Gynecology and Obstetrics (FIGO) stage, pathology. In patients with biochemical recurrence vs. those without, 5-year DFS and OS were 27.6 vs. 92.7% (p ≤ 0.001) and 53.7 vs. 92.5% (p ≤ 0.001), respectively. CONCLUSION: Our study reconfirmed the known function of pretreatment SCC-Ag, but could not confirm the function of biochemical response as a predictive factor for treatment and as a prognostic factor. There was no statistically significant relationship between SCC-Ag level and recurrence site. We confirmed the role of SCC-Ag as a follow-up tool for recurrence of disease and which patient groups SCC-Ag was more useful for.